Age-disparate and intergenerational sex partnerships and HIV: the role of gender norms among adolescent girls and young women in Malawi - Domonique M. Reed; Elizabeth Radin; Evelyn Kim; Nellie Wadonda-Kabondo; Danielle Payne; Myrline Gillot; Andreas Jahn; George Bello; Thokozani Kalua; Jessica E. Justman (BMC, 2024)
Abstract Background Age-mixing (age-disparate [5-9 years difference] and intergenerational [≥ 10 years difference]) partnerships are hypothesized drivers of HIV in adolescent girls and young women (AGYW; 15-24 years). These partnerships are often associated with increased gender inequities which undermine women's agency and assertiveness. We assessed whether age-mixing partnerships were associated with HIV in Malawi and if endorsement of inequitable gender norms modifies this relationship. Methods We analyzed data from the Malawi Population-based HIV Impact Assessment, a nationally representative household survey conducted in 2015-2016. Participants underwent HIV testing and completed questionnaires related to actively endorsed gender norms and sexual risk behavior. We used multivariate logistic regression and multiplicative interaction to assess associations among AGYW who reported the age of their primary sex partner from the last year. Results The analysis included 1,958 AGYW (mean age = 19.9 years, SD = 0.1), 459 (23.4%) and 131 (6.7%) of whom reported age-disparate and intergenerational partnerships, respectively. AGYW in age-mixing partnerships accounted for 13% of all AGYW and were older, more likely to reside in urban areas, to be married or cohabitating with a partner, and to have engaged in riskier sexual behavior compared with AGYW in age-concordant partnerships (p < 0.05). HIV prevalence among AGYW in age-disparate and intergenerational partnerships was 6.1% and 11.9%, respectively, compared with 3.2% in age-concordant partnerships (p < 0.001). After adjusting for residence, age, education, employment, wealth quintile, and ever been married or cohabitated as married, AGYW in age-disparate and intergenerational partnerships had 1.9 (95% CI: 1.1-3.5) and 3.4 (95% CI: 1.6-7.2) greater odds of HIV, respectively, compared with AGYW in age-concordant partnerships. Among the 614 (31% of the study group) who endorsed inequitable gender norms, AGYW in age-disparate and intergenerational partnerships had 3.5 (95% CI: 1.1-11.8) and 6.4 (95% CI: 1.5-27.8) greater odds of HIV, respectively, compared with AGYW in age-concordant partnerships. Conclusions In this Malawi general population survey, age-mixing partnerships were associated with increased odds of HIV among AGYW. These findings highlight inequitable gender norms as a potential focus for HIV prevention and could inform interventions targeting structural, cultural, and social constraints of this key group.